The Role of Social Media in Enhancing Youth Soft Skills for Diplomatic Literacy: A Campus Case Study - Anggi Khairizah Harahap; Putri Hasanah Harahap; Rita Hartati (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Social media has emerged as a transformative platform for youth skill development, particularly in diplomatic literacy. This qualitative study investigates how university students leverage social media to enhance their soft skills, focusing on communication, critical thinking, and cultural sensitivity. Through interviews and focus group discussions with 30 university students, the research explores the mechanisms by which digital platforms facilitate skill development. Findings reveal that social media provides unique opportunities for global interaction, information evaluation, and cross-cultural understanding. Students reported significant improvements in communication skills, critical thinking abilities, and cultural awareness through engaged social media use.